Personality and work motivation as determinants of project success: the mediating role of organisational and professional commitment. (2016) - Dwivedula, Ravikiran; Bredillet, Christophe N.; MÁ¼ller, Ralf
In this study, we set out to explore the relationship between an individual's personality type, and work motivation on project success. We try to understand how an individual's organisational commitment (OC) and professional commitment (PC) mediate this relationship. We present an extensive literature review of the variables of interest and present hypotheses. We observe that interest in studying PC especially in relation to OC has been very recent in case of project management. Further, we found very little literature that focused on studying the influence of OC on project success. Likewise, though there have been research articles that looked at the influence of personality on project success, the possible influence of commitment (both OC and PC) has largely been overlooked. Our proposed model overcomes these limitations.